2011
DOI: 10.1371/journal.pone.0023207
|View full text |Cite
|
Sign up to set email alerts
|

LRRK2 Kinase Activity Is Dependent on LRRK2 GTP Binding Capacity but Independent of LRRK2 GTP Binding

Abstract: Leucine rich repeat kinase 2 (LRRK2) is a Parkinson's disease (PD) gene that encodes a large multidomain protein including both a GTPase and a kinase domain. GTPases often regulate kinases within signal transduction cascades, where GTPases act as molecular switches cycling between a GTP bound “on” state and a GDP bound “off” state. It has been proposed that LRRK2 kinase activity may be increased upon GTP binding at the LRRK2 Ras of complex proteins (ROC) GTPase domain. Here we extensively test this hypothesis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
109
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(117 citation statements)
references
References 38 publications
(74 reference statements)
6
109
0
Order By: Relevance
“…LRRK2 is an active kinase [12][13][14][15], and, as a member of the ROCO family of proteins [16,17], can both bind and hydrolyse GTP [18][19][20]. It was initially proposed that GTP binding could stimulate the kinase activity of LRRK2, although subsequent results suggested that kinase activity of LRRK2 depends on the ability to bind guanosine nucleotides rather than the GTPbound state [21][22][23], an important mechanistic distinction. Reciprocal regulation of GTP binding by the kinase domain may also occur, as LRRK2 autophosphorylates several residues within the ROC domain.…”
Section: Introductionmentioning
confidence: 99%
“…LRRK2 is an active kinase [12][13][14][15], and, as a member of the ROCO family of proteins [16,17], can both bind and hydrolyse GTP [18][19][20]. It was initially proposed that GTP binding could stimulate the kinase activity of LRRK2, although subsequent results suggested that kinase activity of LRRK2 depends on the ability to bind guanosine nucleotides rather than the GTPbound state [21][22][23], an important mechanistic distinction. Reciprocal regulation of GTP binding by the kinase domain may also occur, as LRRK2 autophosphorylates several residues within the ROC domain.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, mutations in the GTPase domain have been demonstrated to increase kinase activity [57,61], whereas in other studies, they have had little or no effect [34,58]. More recent data have shown that the R1441C/G and Y1699C mutations reduced the GTPase activity that in turn regulates kinase activity [14,15]. The majority of studies have used either recombinantly expressed and purified LRRK2 [58] or immunoprecipitated LRRK2 from recombinant mammalian expression systems [34,57,61] and investigated autophosphorylation or the use of surrogate substrates (myelin basic protein, LRRKtide, NICtide), all which are relatively poor substrates under those assay conditions.…”
Section: Effects Of Mutations On Kinase and Gtpase Activitymentioning
confidence: 97%
“…A number of novel variants have been identified in this gene in PD patients, but only seven of these (N1437H, R1441C, R1441G, S1761R, Y1699C, G2019S, and I2020T) can be considered as definitively disease causing, on the basis of co-segregation with disease in families, and an absence in controls [5,[11][12][13]. These mutations either lead to an increased kinase activity (G2019S and I2020T) or to a reduced GTPase activity (R1441C/G and Y1699C), which in turn regulates kinase activity [14][15][16] (vide infra). The G2019S mutation is relatively frequent in some populations from Southern Europe and in certain populations, such as the Ashkenazi Jews and North African Berber Arabs, where the prevalence can be as high as 40% [8].…”
Section: Lrrk2 Genetics and Human Biologymentioning
confidence: 99%
“…LRRK2 autophosphorylation may serve a regulatory function and occurs at residues within or adjacent to the ROC GTPase domain Webber et al 2011;Kamikawaji et al 2013). The GTPase domain of LRRK2 binds guanine nucleotides and is capable of hydrolyzing GTP at a slow rate, apparently independent of its oligomerization state (Ito et al 2007; Lewis et al 2007;Taymans et al 2011;Biosa et al 2013;Liao et al 2014). Although there is evidence for a functional interplay between the two enzymatic domains, the biochemical mechanisms governing LRRK2 enzymatic functions remain unclear.…”
Section: Lrrk2 and Parkinson's Diseasementioning
confidence: 99%
“…Although there is evidence for a functional interplay between the two enzymatic domains, the biochemical mechanisms governing LRRK2 enzymatic functions remain unclear. Interestingly, GTP hydrolysis and GTP binding activities of LRRK2 are both required for LRRK2 kinase activity, whereas the contribution of LRRK2 autophosphorylation within the GTPase domain to GTP binding and GTP hydrolysis activities is incompletely understood (Ito et al 2007;West et al 2007;Taymans et al 2011;Biosa et al 2013). Kinase-inactive variants of LRRK2 exhibit normal GTP binding and GTP hydrolysis activities, although mutation of individual autophosphorylation sites within the GTPase domain (i.e., T1503) can alter kinase activity (Webber et al 2011;Biosa et al 2013).…”
Section: Lrrk2 and Parkinson's Diseasementioning
confidence: 99%